SOUTHTRAC-GW: An Airborne Field Campaign to Explore Gravity Wave Dynamics at the World’s Strongest Hotspot - Rapp, Markus; Kaifler, Bernd; Dörnbrack, Andreas; Gisinger, Sonja; Mixa, Tyler; Reichert, Robert; Kaifler, Natalie; Knobloch, Stefanie; Eckert, Ramona; Wildmann, Norman; Giez, Andreas; Krasauskas, Lukas; et al. (Bulletin of the American Meteorological Society)
The southern part of South America and the Antarctic peninsula are known as the world's strongest hotspot region of stratospheric gravity wave (GW) activity. Large tropospheric winds are deflected by the Andes and the Antarctic Peninsula and excite GWs that might propagate into the upper mesosphere. Satellite observations show large stratospheric GW activity above the mountains, the Drake Passage, and in a belt centered along 60°S. This scientifically highly interesting region for studying GW dynamics was the focus of the Southern Hemisphere Transport, Dynamics, and Chemistry-Gravity Waves (SOUTHTRAC-GW) mission. The German High Altitude and Long Range Research Aircraft (HALO) was deployed to Rio Grande at the southern tip of Argentina in September 2019. Seven dedicated research flights with a typical length of 7,000 km were conducted to collect GW observations with the novel Airborne Lidar for Middle Atmosphere research (ALIMA) instrument and the Gimballed Limb Observer for Radiance Imaging of the Atmosphere (GLORIA) limb sounder. While ALIMA measures temperatures in the altitude range from 20 to 90 km, GLORIA observations allow characterization of temperatures and trace gas mixing ratios from 5 to 15 km. Wave perturbations are derived by subtracting suitable mean profiles. This paper summarizes the motivations and objectives of the SOUTHTRAC-GW mission. The evolution of the atmospheric conditions is documented including the effect of the extraordinary Southern Hemisphere sudden stratospheric warming (SSW) that occurred in early September 2019. Moreover, outstanding initial results of the GW observation and plans for future work are presented. Fil: Rapp, Markus. Ludwig Maximilians Universitat; Alemania Fil: Kaifler, Bernd. Deutsches Zentrum Für Luft- Und Raumfahrt; Alemania Fil: Dörnbrack, Andreas. Deutsches Zentrum Für Luft- Und Raumfahrt; Alemania Fil: Gisinger, Sonja. Deutsches Zentrum Für Luft- Und Raumfahrt; Alemania Fil: Mixa, Tyler. Deutsches Zentrum Für Luft- Und Raumfahrt; Alemania Fil: ...